Financial development and energy consumption: evidence from a heterogeneous panel of Asian countries - Furuoka, Fumitaka (Elsevier, 2015)
This paper examined relationships between financial development and energy consumption in Asia for the period of 1980-2012. For the purpose of the empirical analysis, it performed the heterogeneous panel causality test suggested by Dumitrescu and Hurlin [1]. The findings of the panel cointegration test indicated that there was a long run equilibrium relationship between finance and energy consumption in the region. Moreover, the heterogeneous panel causality test detected a unidirectional causality from energy consumption to financial development but not vice versa. These results indicate that an expansion of energy usage could be a driving force behind financial development in Asia. (C) 2015 Elsevier Ltd. All rights reserved.